Effects of Neurological Disorders on Health Expenditure and Economic Output: Dynamic Panel Analysis for OECD Countries - Yilmaz, Salim; Boz, Canser; Ozsari, Salih Haluk; Yilmaz, Faruk; Turkon, Buse Fidan; Mete, Ani Hande (Mdpi, 2025)
Analyzing the prevalence of neurological disorders (NDs) is crucial to understand health expenditures and economic outcomes as they change over time and have significant economic effects. Diseases, particularly those involving neuron damage, can have an economic impact. This study aims to quantify the effects of NDs on health expenditure and economic output for OECD countries from 2000 to 2021 using a dual-model dynamic panel data approach. Also, this study uniquely highlights the dual economic burden of neurological disorders by examining their simultaneous impact on both health expenditures and economic output using dynamic panel data methods. We used both Arellano-Bond and Blundell-Bond estimation methods. The results indicate that an increase in ND prevalence significantly impacts both health expenditures and economic output. While NDs substantially raise health expenditures, they also decrease income levels, underscoring their dual economic burden. Overall, the rise in NDs in society drives up healthcare spending and underscores their significant economic burden. Policymakers should prioritize preventive strategies and early interventions for neurological disorders to mitigate their rising economic and healthcare costs on a societal level.
Keywords: disease burden; health economics; health expenditure; neurological disorders; panel data analysis